2014
DOI: 10.1111/tpj.12653
|View full text |Cite
|
Sign up to set email alerts
|

High AN1 variability and interaction with basic helix‐loop‐helix co‐factors related to anthocyanin biosynthesis in potato leaves

Abstract: SUMMARYAN1 is a regulatory gene that promotes anthocyanin biosynthesis in potato tubers and encodes a R2R3 MYB transcription factor. However, no clear evidence implicates AN1 in anthocyanin production in leaves, where these pigments might enhance environmental stress tolerance. In our study we found that AN1 displays intraspecific sequence variability in both coding/non-coding regions and in the promoter, and that its expression is associated with high anthocyanin content in leaves of commercial potatoes. Expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
67
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 52 publications
(84 reference statements)
5
67
1
3
Order By: Relevance
“…Sucrose may enhance the synthesis of anthocyanins, but is not capable of causing changes in anthocyanin deficient mutants [65,66]. High intraspecific variability of the StAN1 gene is noted [59,61], with mutations detected both in the coding and non-coding regions (i.e. in the intron 2 and the exon 3 of the gene).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Sucrose may enhance the synthesis of anthocyanins, but is not capable of causing changes in anthocyanin deficient mutants [65,66]. High intraspecific variability of the StAN1 gene is noted [59,61], with mutations detected both in the coding and non-coding regions (i.e. in the intron 2 and the exon 3 of the gene).…”
mentioning
confidence: 99%
“…In another study, the presence of the SINE retrotransposone in the promoter was shown to be associated with anthocyanin pigmentation of leaves. In genotypes with green leaves (without anthocyanin pigmentation), this element does not appear in the StAN1 promoter [59]. The presence of mobile elements modifies the expression of genes encoding MYB [67][68][69][70][71], hence further study of the modification effect of SINE on the StAN1 promoter functions is necessary.…”
mentioning
confidence: 99%
See 3 more Smart Citations